Tindak Pidana Pencemaran Nama Baik Melalui Media Sosial Yang Dilakukan Oleh Anak - Herisasono, Adi; Herawati, Lilik (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2023)
This study aims to analyze the application of diversion to children who commit criminal acts of defamation through social media. The normative juridical method is carried out through analysis obtained from library materials such as books, dictates, and others related to statutory regulations and the concept of jurists as the basis of their research. This study uses a legal concept analysis approach, statutory analysis, and a case approach related to the application of criminal sanctions in cases of defamation. The results of the study concluded that the provisions for criminal defamation through social media are regulated in Article 27 paragraph (3) of Law Number 11 of 2008 concerning Information and Electronic Transactions and cannot be separated from the main legal norms in Article 310 and Article 311 of the Criminal Code as a genus of delict which requires a complaint (klacht) to be prosecuted.